General Issues of Teaching Student Activities in The General Physics Course - Mirzamuratov B. F (Genius Journals, 2021)
The issue of further development of physical education in general and high schools is an objective and legal process. It is determined by the conveniences of scientific and technical revolution and pedagogical science. It is determined by the level of the content of physical education, when the level of physical science will depend. Work is underway to study pedagogical, methodological and polytechnic aspects of the Physics Course. Since the physics of physics is part of natural sciences, the foundation of all natural sciences, and the capacity and quality of specialists are not only determined by their knowledge, skills, the knowledge of scientific thinking, how formed scientific thinking, the level of formation of scientific and discussion. It is also determined. The deep knowledge of general physics will allow students and specialists to adapt their skills with nature
Keywords: Principle; Videotrainer; video; microscope